Collaborative Governance in Preserving the Wehea Customary Forest in Nehas Liah Bing Village, Muara Wahau District, Indonesia - Lorensia Sela; B. Budiman; J. Jumansyah; Sry Reski Mulka (Golden Ratio of Social Science and Education, 2026)
Customary forest management in Indonesia continues to face challenges, including development pressures, land conversion, and weak coordination among actors in natural resource governance. Centralized management approaches are widely considered insufficient to fully ensure forest sustainability and protect the rights of indigenous peoples. This study aims to analyze collaborative governance practices in conserving the Wehea Customary Forest in Nehas Liah Bing Village, Muara Wahau District, East Kutai Regency, Indonesia. The study adopted a qualitative case study design. Data were collected through in-depth interviews, field observations, and document reviews, and analyzed using thematic analysis. The results indicate that the successful management of the Wehea Customary Forest is driven by synergy between the local government, which acts as a policy facilitator; indigenous communities, which play a key role in forest management; and non-governmental organizations, which support capacity building. Furthermore, integrating customary law into the formal governance system has been shown to increase the legitimacy and effectiveness of forest protection and facilitate constructive conflict management. This study concludes that the collaborative governance approach plays a crucial role in conserving customary forests and strengthening recognition of indigenous communities, making it a relevant model for sustainable customary forest management.